The Bombay Samachar Private Limited - Ghosh, Ayan (2023)
Since its inception in 1822, Bombay Samachar changed hands many times. In 1933, the newspaper was taken over by the Cama family who has remained the publisher to this day. The Bombay Chronicle was started in 1910 by Sir Pherozeshah Mehta. From 1913-19, it was edited by B.G. Horniman after whom the Horniman Circle is currently named.